Padrão neuro-comportamental do bruxismo no sono - Azevedo, Marila Rezende (2018)
Bruxism is considered an involuntary repetitive activity of the mandible, involving the masticatory muscles with distinct circadian manifestation and distinct patterns during vigilance (VB) and sleep (SB). Sleep bruxism can lead to simple tooth wear or may affect oro-cranio-cervical muscles by overloading the temporal-mandibular joint. It is more destructive than awake bruxism, as the intensity of contractions during sleep exceeds considerably the capacity of clenching when the individual is awake. In recent papers, SB has been correlated to chronic stress and emotion in modern civilization. Research groups all over the world until now have not reached the conclusion of its aetiology, are looking for its triggering cause, for the most appropriate therapy and in search for what can alleviate its sequel non-invasively, if installed. It has an evident role as a physiological stress relief event controlled and regulated by the central nervous system (CNS) and its autonomic (ANS) branches. Abrupt changes in cortical activity with cardiac hyperactivity, hyperventilation and consequent muscular activation occurs before dental contact and mandibular co-contraction characterizing Sleep Bruxism event. Sleep bruxers may present a peculiar personal mood, which differentiate them from non-sleep bruxers. In daytime are prone to anxiety and stress, have a maladaptive coping skill and exhibit competitiveness. In view of this, 30 samples’ subjects of both genders underwent clinical examinations, anamnesis, plaster cast, photographs, quality of life questionnaires to assess emotional state of anxiety and stress. BiteStrip®, a disposable device was used during a night´s sleep to confirm SB presence or not. In this way, the CNS cortical signals of 30 healthy subjects, 15 from the BS group and 15 from the control group, were collected to identify if sleep bruxers had a different characteristic pattern in wakefulness, triggered by affective images: pleasant, unpleasant and neutral. In the sequence, clinical exams, anamnesis, questionnaires and BiteStrip and cortical data were correlated. The instrument chosen to collect cortical biological signals was electroencephalogram (EEG) with visual evoked potential (VPE). The components (N100, P100, N200, P200, N300 and P300) of related event potentials (ERPs) were used to index early and late changes in neural processes, depending on amplitude and latencies interval, in the presence of passive images from validated database, presented in video. Fp1, Fp2, F4 and F7, had higher amplitudes for neural answers in the EG statistically significant, more than the GC subjects. The same occurred with latency were in channels Fp1, O2, T5, T6, P3, C3 the components were anticipated more in EG than in the control group. The result proved that there is difference between the subjects of the experimental and control groups with respect to neural and behavioural pattern in the period of wakefulness. Along with the information gathered by clinical examination, ananmeses, specific questionnaires and Bitestrip®, where anxiety demonstrated a strong and statistically significant correlation in the SB group, in relation to the control group (CG). This study proved that SB subjects present a distinct behavioral pattern that influences the cortical activity, which occurs during the day, and can be detected by VEP means. It was concluded that the visual evoked potentials are useful tools for understanding the emotional states of the depths of the human brain. By identifying the cortical activity of the ERP, you can plot a profile of the subject and plan for behavior-focused therapy, in addition to dental and pharmacological practices. The hypothesis has been confirmed that neuro-behavioural pattern is different between Sleep Bruxers (SB) and non-Bruxers.